A non-parametric and multidirectional model in quantitative research - Murillo, Kelly Patricia (2021)
In this work, a non-parametric and deterministic approach based on multidirectional efficiency analysis (MEA) is presented. The proposed model involves MEA with other important mathematical techniques in data analysis, such as the calculation of the NC value for the analysis of groups with different levels of efficiency. This model allows us to examine the factors that influence the behavior of decision-making units in different contexts such as business efficiency, educational quality, energy efficiency, circular economy, among others. Particularly in this work, we show the results obtained in 1787 Portuguese companies in the materials manufacturing sector (manufacture of wood and paper; manufacture of rubber products, plastics and other non-metallic mineral products; manufacture of common metals and metallic products, except machinery and equipment) in an eight-year period (2006-2013) of study. The results allow, not only a characterization of the financial structure of the sector and a diagnosis through indices that identify the strategic positioning of companies in terms of efficiency scores; but also a characterization of the most efficient units and an analysis of the variables that must be addressed differently, to obtain better results, in terms of economic performance.